Pengaruh Model Pembelajaran Inquiry dan Direct Instruction Terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Dasar Teknik Elektronika Kelas X TEI di SMKN 1 Nglegok Blitar - Diah Wahyu Puji Lestari; Meini Sondang Sumbawati; Tri Rijanto; Puput Wanarti Rusimamto (Indo Publishing, 2026)
This study aims to analyze the differences in the results of Basic Electronic Engineering (DTE) learning between students who use the inquiry learning model and X TEI class direct instruction at SMKN 1 Nglegok Blitar. Next, analyze the improvement in DTE learning outcomes using the Inquiry learning model, then analyze the improvement in DTE learning outcomes using the X TEI class direct instruction learning model at SMKN 1 Nglegok Blitar. This study used an experimental method with a quasi experimental design. Experimental class using Inquiry learning model with a sample of 35 students and control class with Direct Instruction learning model with a sample of 36 students. Data collection instruments include pretest and posttest for measuring cognitive, attitude observation sheets for measuring affective, and skill observation sheets for measuring psychomotorical learning outcomes. Data analysis techniques include normality test, homogeneity test, t-test (independent sample-test), and N-Gain test with the aid of version 25 SPSS software.The research results show that there are differences in DTE learning outcomes in both classes. The average posttest grade of the experimental class was 87.37, and the posttest grade of the control class was 76.53. The results of the independent sample-t test showed a significant difference in the knowledge aspect (sig < 0.05). Experimental class DTE learning results obtained pretes (68.23) and posts (87.37). An N-Gain value of 0.5892 (medium) was thus obtained. The DTE learning results for the control class were obtained pretest (67.22) and posts (76.53), and the N-Gain was obtained by 0.2658 (low). In the attitude aspect, the average observation score of the experimental class was 84, higher than the control class of 79. Similarly, in terms of skill, the average grade of experiment class is 88 and the control class is 75. Thus, it can be concluded that the use of Inquiry learning models is more effective than Direct Instruction to improve the learning outcomes of DTE of students.